Theory of magnetization dynamics in a dual-free-layer spin-torque nano-oscillator with isotropic free layers - Prokopenko, O.V.; Tiberkevich, V.S.; Slavin, A.N. (Functional Materials, 2014)
The analytical theory of magnetization dynamics in a dual-free-layer spin-torque nano-oscillator (DFL STNO) operating in the absence of a bias magnetic field is developed. The theory is based on a system of simplified dynamic equations written in collective variables and yields an analytic expression for the upper dc current density threshold of stable magnetization dynamics (generation) in the DFL STNO. This threshold is caused by a dipolar coupling between the free layers and can be controlled by choosing an appropriate geometry of the DFL STNO structure.